AN ANALYSIS OF SYMBOLISM IN DIAMONDS AND TOADS DRAMA SCRIPT AND ITS FUNCTION IN BUILDING MORAL VALUES - Devi Triana; Mutiara Angelica Sinaga; Yena Jorena Sembiring; Yolanda Jesica Sitanggang; Tessaria Simorangkir; Nessa Lumbantobing; David Togi Hutahaean (STKIP Subang, 2026)
This study analyzes the symbols in the drama script Diamonds and Toads by Charles Perrault and examines their function in building moral values. A descriptive qualitative method was applied, with data collected from the drama script adapted from Perrault's fairy tale. The analysis was conducted using Miles and Huberman's interactive model (data reduction, data display, and conclusion drawing) combined with Roland Barthes' semiotic theory, which distinguishes denotation (literal meaning) and connotation (symbolic meaning). The findings reveal three categories of symbols: object symbols (40.91%), character symbols (31.82%), and place/event symbols (27.27%). Object symbols such as roses, pearls, and diamonds connote goodness and virtue, while vipers and toads connote evil and vice. Character symbols position the younger daughter as a symbol of humility and the elder daughter as a symbol of arrogance. Place symbols such as the fountain represent moral testing, the forest symbolizes exile and protection, and the palace represents reward. The symbols function through binary oppositions such as flowers versus snakes, humility versus pride, service versus selfishness, to convey the central moral message that good deeds produce good results and evil deeds produce evil results. The symbols serve four functions: providing concrete representations of abstract moral concepts, creating emotional resonance, serving as memory aids, and establishing a clear moral structure. This study contributes to literary studies, particularly in semiotics and symbol analysis in drama scripts, and offers practical benefits for educators and students in understanding moral values in literary works.